A putative RND-type efflux pump, H239_3064, contributes to colistin resistance through CrrB in Klebsiella pneumoniae. (28th February 2018) - Cheng, Yi-Hsiang; Lin, Tzu-Lung; Lin, Yi-Tsung; Wang, Jin-Town
Abstract: Background: Colistin is one of the last-resort antibiotics used to treat carbapenem-resistant Klebsiella pneumoniae infection. Our previous studies indicated that clinical strains encoding CrrB with amino acid substitutions exhibited higher colistin resistance (MICs ≥512 mg/L) than did colistin-resistant strains encoding mutant MgrB, PmrB or PhoQ. Objectives: CrrAB may regulate another unknown mechanism(s) contributing to colistin resistance, besides modifications of LPS with 4-amino-4-deoxy-l -arabinose and phosphoethanolamine. Methods: To identify these potential unknown mechanism(s), a transposon mutant library of A4528 crrB (N141I) was constructed. Loci that might contribute to colistin resistance and were regulated by crrB were confirmed by deletion and complementation experiments. Results: Screening of 2976 transposon mutants identified 47 mutants in which the MICs of colistin were significantly decreased compared with that for the parent. Besides crrAB, crrC and pmrHFIJKLM operons, these 47 transposon insertion mutants included another 13 loci. Notably, transcript levels of one of these insertion targets, H239_3064 (encoding a putative RND-type efflux pump), were significantly increased in A4528 crrB (N141I) compared with the A4528 parent strain. Deletion of H239_3064 in the A4528 crrB (N141I) background resulted in an 8-fold decrease in the MIC of colistin; complementation of the deletion mutant with H239_3064 restored resistance to colistin. Susceptibilities of A4528-derived strains to other antibiotics were also tested. Mutations of crrB resulted in decreased susceptibility to tetracycline and tigecycline, and deletion of H239_3064 in A4528 crrB (N141I) attenuated this phenomenon. Conclusions: This study demonstrated that missense mutations of K. pneumoniae crrB lead to increased expression of H239_3064, leading in turn to decreased susceptibility to colistin, tetracycline and tigecycline.